Tetanus Toxoid Injection During Last Pregnancy Among Women in Reproductive Age in Nepal - Mikrani, Ashfaque Raza; Sari, Marlynda Happy Nurmalita (Balai Publikasi Indonesia, 2024)
Tetanus toxoid injection is important as one mandatory vaccine for pregnant women to prevent maternal and neonatal tetanus. This study purposed to examine the barriers of not receiving tetanus toxoid vaccine among women of reproductive age in Nepal. This study used the secondary data using “Multiple Indicators Clusters Survey” round 6 in 2019. Total sample of this study are 2,494 women of reproductive aged 15 to 49 years. The data analysis was done for univariate, bivariate, and multivariate using binary logistic regression. The results in this study revealed that increasing child ever born (CEB) as the main predictor for not receiving TT vaccine, following by higher educational level and wealth index. In conclusion, the TT vaccine is a critical intervention to prevent maternal and neonatal tetanus. Understanding the determinants of TT vaccination coverage, ensuring accessibility to the vaccine, and addressing knowledge gaps among pregnant women are essential for improving TT vaccination rates during pregnancy